Sir Robert Anderson, K.C.B., LL.D. and Lady Agnes Anderson - Moore-Anderson, Arthur P. (London, UK Marshall, Morgan and Scott, 1947)
Includes photographs.
Brethren writer.
Keywords: Anderson, Robert, -- Sir, -- 1841--1918; Brethren movement -- biography